2020
DOI: 10.1002/2211-5463.12933
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The F‐box protein FBXO11 restrains hepatocellular carcinoma stemness via promotion of ubiquitin‐mediated degradation of Snail

Abstract: FBXO11 expression is down‐regulated in various tumors, but its role in hepatocellular carcinoma remains unclear. Here, we examined the role of FBXO11 in hepatocellular carcinoma cell stemness. FBXO11 overexpression decreased Snail protein levels by directly interacting with Snail and promoting Snail degradation through the ubiquitin‐proteasome system. Overexpression of Snail rescued the inhibitory effect of FBXO11 overexpression on cell stemness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…It is also thought to play a role in maintenance of genome stability ( 12 ). Its function has mainly been studied in the context of different malignancies such as B-cell lymphoma ( 10 ), myelodysplastic syndrome ( 13 ), hepatocellular carcinoma ( 14 ), gastric cancer ( 15 ) and glioblastoma ( 16 ). The functional role of FBXO11 in neurodevelopmental disorders (NDDs) and neurodevelopment in general remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It is also thought to play a role in maintenance of genome stability ( 12 ). Its function has mainly been studied in the context of different malignancies such as B-cell lymphoma ( 10 ), myelodysplastic syndrome ( 13 ), hepatocellular carcinoma ( 14 ), gastric cancer ( 15 ) and glioblastoma ( 16 ). The functional role of FBXO11 in neurodevelopmental disorders (NDDs) and neurodevelopment in general remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of such MHC-II expression has not been elucidated, it has been proposed that MHC-II expression in tumors, called tumor-specific MHC-II (ts-MHC-II), plays a part of significant roles in cancer immunity in a variety of tumor types, and high expression of ts-MHC-II is associated with a favorable prognosis and responsiveness to immune checkpoint inhibitors ( 3 5 , 42 ). While tumor-related proteins such as BCL6, p53, SNAIL1, and BLIMP1 are known substrates of FBXO11, the role of FBXO11 in cancer is not yet clear ( 30 , 40 , 47 52 ). We examined the relationship between these FBXO11 substrates and survival of breast cancer patients and found that expression levels of BCL6 , TP53 , and SNAI1 had no effect on overall survival ( SI Appendix , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitination analysis was constructed under denaturing condition and the detailed procedure was referred to the previous work 22 . Briefly, recombinant proteins were incubated in 40 mM Tris‐HCl (pH 7.6), 50 mM NaCl, and 1 mM dithiothreitol with 100 ng of an E1 (UBE1; Boston Biochem), 250 ng of an E2 (UbcH5c; Boston Biochem), 5 μg of ubiquitin (sigma), and 2 mM ATP (Fermentas) for 3 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The ubiquitination analysis was constructed under denaturing condition and the detailed procedure was referred to the previous work. 22 Briefly, recombinant proteins were incubated in 40 mM Tris-HCl…”
Section: Ubiquitination Analysismentioning
confidence: 99%